2013
DOI: 10.1038/ajg.2013.152
|View full text |Cite
|
Sign up to set email alerts
|

Luminal Cysteine-Proteases Degrade Colonic Tight Junction Structure and Are Responsible for Abdominal Pain in Constipation-Predominant IBS

Abstract: These data suggest that luminal CPs may represent a new factor contributing to the genesis of symptoms in IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 39 publications
4
77
0
2
Order By: Relevance
“…In line with these findings, serine proteases in faecal supernatants from individuals with IBS-D evoked colonic hypersensitivity to distension 44 . By contrast, faecal cysteine protease activity was augmented in some patients with IBS-C compared with controls and increased protease activity correlated with abdominal pain and impaired epithelial permeability 45 . Further work showed the implication of serine proteases that act on protease-activated nociceptors located on intestinal nerves conveying pain stimuli to the brain 43 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 73%
“…In line with these findings, serine proteases in faecal supernatants from individuals with IBS-D evoked colonic hypersensitivity to distension 44 . By contrast, faecal cysteine protease activity was augmented in some patients with IBS-C compared with controls and increased protease activity correlated with abdominal pain and impaired epithelial permeability 45 . Further work showed the implication of serine proteases that act on protease-activated nociceptors located on intestinal nerves conveying pain stimuli to the brain 43 .…”
Section: Mechanisms/pathophysiologymentioning
confidence: 73%
“…151,152 Different proteases seems to be of importance in different clinical situations: serine proteases have been found to be elevated in IBS-D, 152 and cysteine proteases in patients with IBS-C. 151 Cysteine proteases have a degrading effect on occludin in mice and also in the human colonic epithelial T84 cell line, and this pathogenetic mechanism can be supported by the finding of decreased occludin levels in mucosal biopsy samples from patients with IBS-C. 151 A steadily increasing number of studies support that increased intestinal permeability in patients with IBS is linked to enhanced activity of the immune system, and a link with food allergy has been suggested. 153 Experiments in colon explants from mice have shown that the interaction between TNF and neuropeptide Y results in increased intestinal permeability.…”
Section: Putative Causes Of Altered Gut Permeabilitymentioning
confidence: 97%
“…Recently, the Spiller group published a paper demonstrating the human (and not bacterial) origin of the most abundant fecal serine proteases in IBS-D patients[52]. Cysteine protease activity was elevated in fecal samples of IBS-C patients[53], although this alteration could not be observed in colonic samples of post-infectious IBS mice[51]. Recently, concerns have been raised about the tests used to determine the protease activity.…”
Section: Proteases Protease-activated Receptors and Protease Inhibitmentioning
confidence: 99%